Preparation, Characterization, and Release Kinetics of Chitosan-Coated Nanoliposomes Encapsulating Curcumin in Simulated Environments - Hasan, Mahmoud (Molecules, 2019)
Curcumin, a natural polyphenol, has many biological properties, such as anti-inflammatory, antioxidant, and anti-carcinogenic properties, yet, its sensitivity to light, oxygen, and heat, and its low solubility in water renders its preservation and bioavailability challenging. To increase its bioaccessibility, we fabricated nanoliposomes and chitosan-coated nanoliposomes encapsulating curcumin, and we evaluated the systems in terms of their physicochemical characteristics and release profiles in simulated gastrointestinal mediums. Chitosan-coating enhanced the stability of nanoliposomes and slowed the release of curcumin in the simulated gastrointestinal (GI) environment. This study demonstrates that nanoliposomes and chitosan-coated nanoliposomes are promising carriers for poorly soluble lipophilic compounds with low oral bioavailability, such as curcumin.